Teacher’s Effort In Improving Student Intrapersonal Intelligence Through Student Facilitator And Explaining (SFAE) Method In IPS Learning - Prisani, Aulia (Universitas Pendidikan Indonesia, 2017)
This study is motivated by the low of students intrapersonal intelligence in IPS learning and still lack of implementation of learning method that can improve students intrapersonal intelligence. The formulation of the problem that will be answered in this study is how the learning plan implemented by the teacher to improve students intrapersonal intelligence through Student Facilitator And Explaining method (SFAE), how the implementation of learning by teachers to improve students intrapersonal intelligence through SFAE method and how the obstacles encountered by teachers in attempt to improve students#39; intrapersonal intelligence through the SFAE method. The purpose of this study is to describe the efforts of teachers in improving students#39; intrapersonal intelligence in IPS learning through SFAE method. This study method is descriptive study by using data collecting technique of interview, observation and documentation study. The subjects of this study are IPS teachers and 33 students of class VIII-K. Based on the data obtained, the following results are obtained. First, IPS learning planning using SFAE method has been prepared and prepared by teachers well, teachers are guided by the syllabus and pay attention to RPP components. Second, the implementation of the SFAE method in improving the intrapersonal intelligence goes well, the teacher carries out the learning with respect to the provisions and learning steps in accordance with the SFAE method. Third, the obstacles encountered in applying the SFAE method to improve students #39;intrapersonal intelligence are the lack of students#39; knowledge of the SFAE method and concept maps as well as the limited time available for learning execution. The solution to solve the problem is the teacher should introduce the learning method used, introduce the concept map and manage the learning time effectively.